Zoonoses in dog and cat shelters in North-East Italy: update on emerging, neglected and known zoonotic agents - Mazzotta, Elisa; Lucchese, Laura; Corrò, Michela; Ceglie, Letizia; Danesi, Patrizia; Capello, Katia; Natale, Alda (Frontiers in Veterinary Science, 2024)
IntroductionShelters for stray dogs and cats deserve careful monitoring for zoonotic risk, as they represent a crucial point for prevention and control of infection spread. Data sorting to prioritize zoonotic agents in a geographic area need constant updating, but no regular official programs are ongoing, to allow an efficient risk survey for these animal species. This study aimed to conduct a comprehensive investigation of the prevalence of certain known, potential and emerging zoonoses within the framework of the routine monitoring of dog and cat shelters in North-East Italy.MethodsA total of 389 cats and 257 dogs housed in public veterinary services shelters and feline colonies were included in the present investigation. The animals originated from the provinces of Padua, Venice, Rovigo, Vicenza, Verona, Trento and Bolzano. Serological, molecular and microbiological diagnostics were implemented to investigate the prevalence of Leptospira sp., Brucella canis, Leishmania infantum, dermatophytes, gastrointestinal parasites, antimicrobial-resistant bacteria, Capnocytophaga sp., Bartonella sp., Norovirus, Rotavirus A, Cowpox virus, Mammalian Orthoreovirus, Hepatitis E virus, SARS-CoV-2 and Influenza A virus.ResultsData about some known zoonoses (e.g., serological positivity of Leishmania infantum 25% and Leptospira sp. 44.3% in dogs, and Bartonella henselae 70% in cats) resulted aligned with previous research and recent reports, whereas there was a notable occurrence of some potential, emerging and neglected pathogens (e.g., Mammalian Orthoreovirus 0.38% in dogs and 2.83% in cats). For some other agents (e.g., dermatophytes in dogs and in cats) the prevalence resulted lower than expected.DiscussionThe prevention of the zoonotic risk requires a re-examination of the complex interaction between humans, animals, and environment. This is of particular importance in settings like companion animal shelters, which serve as key sites for disease monitoring and zoonotic risk mitigation. The study highlights the need to monitor and prioritize the zoonotic pathogens, to implement and constantly update surveillance and specific training programs for the kennels’ operators, and management of epidemiological risks.